2013
DOI: 10.5539/jas.v5n4p161
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Analysis of New Varieties of Citrus as a Complementary Strategy to the Brazilian Citriculture

Abstract: In Brazil new varieties of citrus were selected along the years, but none sensory analysis is usually made to verify the acceptance as one of the bottleneck for fresh citrus juice industry and before the commercial release. We have evaluated the response of consumers (n=62) for eight new hybrids of the crossing between sweet orange and mandarin in five sensory attributes and used analysis of variance Tukey's procedure (HSD) and internal preference mapping for the data processing. The results were compared in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Their juice had 52.2 AE 0.9 mg of ascorbic acid/100 mL of juice, pH 3.8 AE 0.1, 0.62 AE 0.1% of citric acid, and 12.8 AE 0.3 Brix of total soluble solids; corresponding to a maturity index of 20.8 AE 0.5. Castro et al (2013) reported similar results for the same mandarin variety, a weight of 136.4-223.9 g, with 36.0-52.2 % of that weight corresponding to juice, 0.73-1.01 % of citric acid and 7.4-12.1 Brix, corresponding to maturity indexes between 4.4 and 12.0. de Borges and Pio (2003) also found comparable characteristics, with weight between 149.5 and 179.0 g with 50.4-53.5 % of it as juice, 0.9-1.4 % of citric acid and 10.3 to 13.2 Brix, corresponding to 6.9 to 16.7 of maturity index. Variations in properties are attributed to the fruits being grown in diverse locations under different climates and soil compositions (Kader, 2008).…”
Section: Resultssupporting
confidence: 57%
“…Their juice had 52.2 AE 0.9 mg of ascorbic acid/100 mL of juice, pH 3.8 AE 0.1, 0.62 AE 0.1% of citric acid, and 12.8 AE 0.3 Brix of total soluble solids; corresponding to a maturity index of 20.8 AE 0.5. Castro et al (2013) reported similar results for the same mandarin variety, a weight of 136.4-223.9 g, with 36.0-52.2 % of that weight corresponding to juice, 0.73-1.01 % of citric acid and 7.4-12.1 Brix, corresponding to maturity indexes between 4.4 and 12.0. de Borges and Pio (2003) also found comparable characteristics, with weight between 149.5 and 179.0 g with 50.4-53.5 % of it as juice, 0.9-1.4 % of citric acid and 10.3 to 13.2 Brix, corresponding to 6.9 to 16.7 of maturity index. Variations in properties are attributed to the fruits being grown in diverse locations under different climates and soil compositions (Kader, 2008).…”
Section: Resultssupporting
confidence: 57%
“…al., 2010). Following this trend, CASTRO et al (2013) observed that some hybrids between tangerine and sweet orange (TM x LP 222 and TC x LP 5) had aptitude for the juice industry and potential varieties for fresh fruit market. In another research PACHECO et al (2014) describe that samples processed (juice) and fresh (fruit) of hybrid TMxLP 290 have found that the had 84% and 81% approval respectively, indicating good acceptance by the tasters, being options for citrus market in the future.…”
Section: Termos De Indexaçãomentioning
confidence: 86%
“…This Zn defi ciency is common in Brazil and potentially results from phosphate fertilization (Costa and Oliveira, 2001). The Fe concentrations varied Castro et al (2013) assessed the juice yield, TSS and TSS/TTA in several types of oranges and found RS values within the ideal and acceptable range. The TSS values ranged from 7 to 12 ºBrix, and the TSS/TTA values ranging from 4 to 11 ºBrix.…”
Section: Resultsmentioning
confidence: 99%